PENGARUH PEMADATAN TERHADAP KARAKTERISTIK KUAT GESER TANAH LEMPUNG EKSPANSIF - Simangunsong, Yoel Febrian; Mulyati, Ely; Pramudwitya, Petrus Kanisius Tegar (Ensiklopedia of Journal, 2025)
Soil is one of the primary materials in construction, serving as the medium that supports the loads of buildings and other infrastructure. The stability of the structures built on it greatly depends on the physical and mechan- ical properties of the subgrade soil. However, not all soils possess characteristics that are ideal for construc- tion. One type of soil that often poses technical problems is expansive clay. This soil is known for its tendency to swell when wet and shrink when dry due to its high content of active clay minerals. Not all soils are suitable for use in construction, as some subgrade types have issues related to both bearing capacity and settlement (Lestari & Lestari, 2014). Therefore, expansive clay requires special treatment before it can be used as a construction medium. One common technique for improving soil properties is compaction (Diana et al., 2022). Compaction is carried out to increase the dry unit weight of the soil, reduce porosity, improve bearing capac- ity, and minimize the potential for volume change due to variations in water content. In general, compaction alters several soil characteristics, such as dry density, void ratio, shear strength parameters, and soil volume (Lubis, 2007). Through compaction, it is expected that the soil will become more stable both structurally and mechanically. To determine the optimal compaction condition, a laboratory test known as the Standard Proctor Test is conducted. On the other hand, to assess the extent of improvement in the mechanical properties of soil after compaction, a shear strength test such as the Unconfined Compression Test (UCT) is used. UCT is a simple method for measuring the strength of cohesive soils without the application of confining pressure. Shear strength is the soil's ability to resist shear stress when subjected to loading (Agustina & Elfrida, 2019). Through this test, the value of Unconfined Compressive Strength (qu) can be obtained, which can then be used to determine the undrained shear strength (su) of the soil. The combination of the Standard Proctor Test and the Unconfined Compression Test becomes essential in analyzing the relationship between compaction level and the shear strength characteristics of expansive clay. Water content during compaction plays an important role in determining the values of unconfined compressive strength and shear strength. Expansive clay samples compacted at optimum moisture content (OMC) using the Standard Proctor method yield the highest compres- sive and shear strength values (Yunus & Annisa, 2023). Keywords: Compaction, Shear Strength, Expansive Clay Soil, Water Content